The Evolution of Academic Libraries in the Age of Technology - Saharkhiz, Yasaman; Valizadeh, Majid; Salamat, Hengameh (Journal of History Culture and Art Research, 2017)
In the present age, one of the main elements in every country is information and its role in the development of countries. In such an era, universities are pioneers in development and knowledge production in which, academic libraries also play a significant role. In the design field, libraries that have long been synonymous with peace and tranquility are now considered as a place in which there should be a balance between quiet atmosphere and social dynamic mood. The aim of this study is to examine the evolution of spaces of academic libraries, which is constantly being changed as a result of technological advancements and alteration of old systems with new ones. Our research method includes reviewing similar domestic samples, conforming examples to library standards and examining the changing process of several foreign libraries over a period of time. The results of this study indicate that generally, modern libraries have fewer spaces for paper books and publications and individual study, instead, more spaces are dedicated to places for group studies and using computer. This change has influenced the function of the spaces, the relation between different parts of the library and people who use it.